Voynich Manuscript Latin Translation / Thomas O'Neil - O'Neil ,Thomas
TheVoynich Manuscriptis an extensively illustrated codex featuring cosmological and astrological diagrams interwoven with detailed herbal illustration, relating both to the magical and alchemic view of the universe. It is written in a strangely beautiful cryptographic script.